IMPROVING ELEMENTARY SCHOOL STUDENTS MOTIVATION AND SPIRIT IN LEARNING TECHNOLOGY IN EVERYDAY LIFE - Rima Tamara Aldisa (Adisam Publisher, 2024)
This research aims to increase the motivation and enthusiasm of elementary school students in learning technology. With technology becoming an important part of everyday life and the importance of mastering technology skills in the digital era, this research forms a strategy to build positive attitudes towards technology learning among elementary school students. Through surveys, interviews and direct observations, this research also investigates various factors that influence students' level of motivation in technology education. In addition, innovative teaching creates a fun learning environment and stimulates curiosity and interest in technology-related subjects. This research provides valuable insight into effective strategies or ways for educators and policy makers to build enthusiasm and enthusiasm for learning technology among students at the elementary school level in everyday life.